SIGNIFICANT SYMBOLS OF PHYTOMORPHIC ORNAMENTS OF BYZANTINE GOLDSMITHERY IV–IX CENTURIES - Барбалат, О. В. (Art and Design, 2021)
Purpose of the research is to analyse of the peculiarities of the symbolic meaning and specific use of phytomorphic ornamentation in Byzantine goldsmithery of the IV–IX centuries. Methodology.The research is applied historical-cultural and art critic approaches combined with comparative and presentational methods. Results.The results of the research prove the relationship between Eastern and Greco-Roman traditions of using floral ornamentation in Byzantine jewellery in the IV–IX centuries is highlighted. The traditions and application of floral ornamentation in Byzantine jewellery of the indicated period are identified. The system of transformation of plant motifs into meaningful symbols of spiritual truth embedded in Christianity is analysed. The stylistics, symbolic meaning and artistic peculiarities of plant ornaments applied in jewellery of the above period are investigated on the example of outstanding jewellery items. Jewellery items decorated with floral ornaments from the early Byzantine and iconoclastic periods from renowned museum collections worldwide are examined. The peculiarities of the sign symbolism of phytomorphic ornaments in the Byzantine jewellery of the IV–IX centuries are identified. Artistic technologies and terminology of the Byzantine goldsmith's period are characterized and specified. Scientific novelty. The sign symbolism of phytomorphic ornaments in the Byzantine goldsmith's art of the IV–IX centuries was investigated in a comprehensive way. The causes for the use of phytomorphic ornaments in jewellery items of that time as elements specifying Christian images at certain stages of their canonical formation have been revealed. The article proves the importance of the use of the sign symbolism of phytomorphic ornaments in Byzantine jewellery for further qualitative formation and perfection of Christian traditions. Practical significance. The material of this research can be reflected in the writing of academic disciplines related to artistic technologies in jewellery. As a source of inspiration they can be applied in the process of creating new jewellery collections of Christian themes.